VALU 1994 - SVT exit poll survey EU-referendum 1994 - Näsman, Per; Hernborn, Hans; Holmberg, Sören; Thedéen, Torbjörn (Sveriges Television, 2008)
Swedish exit poll surveys was carried out in connection with the elections in 1991and 1994, and they were followed by a similar survey in connection with the referendum on Swedish membership in the European Union. Voters leaving the polling stations were asked to fill in a questionnaire including questions on: altenative voted for in the referendum; time for decision how to vote; party voted for in the general election 1991; vote intention at the referendum on Swedish EU-membership; placement on a political left-right scale; confidence in Swedish politicians; gender, age, occupational group and union membership. The respondents also had to indicate how important a number of items were for the decision how to vote, and to give an opinion on the policy of the different political parties.

Purpose:

Provide analytical support for the election night broadcast on Swedish television during the election night, and for other post-election analysis.

Swedish exit poll surveys was carried out in connection with the elections in 1991 and 1994, and they were followed by a similar survey in connection with the referendum on Swedish membership in the European Union. Voters leaving the polling stations were asked to fill in a questionnaire including questions on: altenative voted for in the referendum; time for decision how to vote; party voted for in the general election 1991; vote intention at the referendum on Swedish EU-membership; placement on a political left-right scale; confidence in Swedish politicians; gender, age, occupational group and union membership. The respondents also had to indicate how important a number of items were for the decision how to vote, and to give an opinion on the policy of the different political parties.

Syfte:

Ge ett analysunderlag för den valvaka som sändes i Sveriges Television under valkvällen, samt för andra eftervalsanalyser.
VALU 1994 - SVT:s vallokalsundersökning folkomröstningen 1994
VALU94EU
Keywords: elections; val; religious attendance; religiöst deltagande; trust; förtroende; exit polls; vallokalsundersökningar; voting; röstning; parliamentary elections; riksdagsval; european union; europeiska unionen; trade union membership; medlemskap i fackförening; voting behaviour; väljarbeteende; political participation; politiskt deltagande; election data; valdata; referendums; folkomröstningar; electors; väljare; political parties; politiska partier; election campaigns; valkampanjer; electoral issues; valfrågor; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap